1988
DOI: 10.1111/j.1540-8159.1988.tb03988.x
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Pacing Catheters: A Survey of Safety and Efficacy

Abstract: We surveyed 12 medical centers with regard to the reuse of pacing catheters during electrophysiologic studies. The prevalence of superficial skin infections or bacteremia related to EP studies was extremely low, and was not significantly different in the catheter reuse group compared to the single use group. We conclude that catheter resterilization and reuse is safe and cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 1 publication
0
10
0
2
Order By: Relevance
“…The criticisms that can be made of these studies are that one was a retrospective survey that depended on the memory of those who responded. 9 It is possible that isolated events escaped the attention of the participants in the survey or they may have forgotten complicating events. The other prospective studies involved smaller numbers of patients.…”
Section: Limitations Of Available Clinical Datamentioning
confidence: 99%
“…The criticisms that can be made of these studies are that one was a retrospective survey that depended on the memory of those who responded. 9 It is possible that isolated events escaped the attention of the participants in the survey or they may have forgotten complicating events. The other prospective studies involved smaller numbers of patients.…”
Section: Limitations Of Available Clinical Datamentioning
confidence: 99%
“…However, a study comparing infection risk in patients undergoing cardiac catheterization with disposable versus reprocessed catheters found that no patient developed infection (Frank et al, 1988). Similarly, in a survey of 12 large medical centers, reuse of pacing catheters was common and was not associated with postprocedure infections (O'Donoghue and Platia, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Le specie Bacillus sono state impiegate per la loro documentata resistenza alla sterilizzazione a bassa temperatura, (14)(15)(16)(17)(18) utilizzando colture in cui è stata verificata la presenza sia di forme vegetative che sporali. Enterococcus faecium e Escherichia coli sono ceppi rappresentativi di batteri Grampositivi e Gram-negativi ampiamente diffusi e potenzialmente patogeni e per questo indicati in letteratura come ceppi utili alle valutazioni microbiologiche per la convalida della rigenerazione di dispositivi medici monouso (8).…”
Section: Materiali E Metodiunclassified
“…Da un'analisi della letteratura emergono dati contrastanti circa la sicurezza e l'efficacia di un possibile riutilizzo dei SUDs (1,2,7,9,17). Al giorno d'oggi, la cardiologia interventistica rappresenta uno dei campi in cui questa procedura sembra maggiormente indicata per sicurezza ed efficacia.…”
Section: Introduzioneunclassified